Description of four new species in the bee genus Melitta Kirby, 1802 (Hymenoptera: Melittidae) - Michez, Denis; Kuhlmann, Michael; Ivanov, Sergey P.; Radchenko, Vladimir G. (Zootaxa, 2012)
Four new bee species of the genus Melitta Kirby, 1802 are here described: Melitta (Cilissa) singular Michez sp. nov. fromEast-Anatolia (Turkey), Melitta (Cilissa) budashkini Radchenko & Ivanov sp. nov. from Crimea (Ukraine), Melitta (Ci-lissa) engeli Michez sp. nov. from Kyrgyzstan and Melitta (Cilissa) magnifica Michez sp. nov. from Mongolia. An updated checklist of Melitta species of the world is provided.